Dispositivo para ensaio automático de sedimentação e análise granulométrica do solo - Martins, Daniel Warles Pereira (2018)
This work presents a device and method for the recognition of soil physicochemical properties. The proposed device measures the behavior of the particles in sedimentation using the principle of photo sedimentation in multipoints. For each soil submitted to the test in the device, a matrix is generated that corresponds to the behavior of the soil. This matrix is submitted to pattern recognition using artificial neural network, which identifies the soil type and by association in the database, presents the best classification for the soil tested. The results show that the measurements carried out in the multipoints provide significant information on soil sedimentation behavior.